80.0k views
3 votes
What is the answer to -12 = 4(f-6)

User Raiyan
by
5.7k points

1 Answer

2 votes

Answer:

Explanation:

-12 = 4(-6 + f)

-12 = (-6 * 4 + f * 4)

-12 = (-24 + 4f)

-12 = -24 + 4f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-4f' to each side of the equation.

-12 + -4f = -24 + 4f + -4f

Combine like terms: 4f + -4f = 0

-12 + -4f = -24 + 0

-12 + -4f = -24

Add '12' to each side of the equation.

-12 + 12 + -4f = -24 + 12

Combine like terms: -12 + 12 = 0

0 + -4f = -24 + 12

-4f = -24 + 12

Combine like terms: -24 + 12 = -12

-4f = -12

Divide each side by '-4'.

f = 3

Simplifying

f = 3

Hope helps you

User Jesvin Jose
by
5.3k points